Campusübergreifende Lehrforschung in verschiedenen Modulen im Studiengang Marketing-Management zum Thema Nachhaltigkeit - Cansu Hattula; Julia Hilgers-Sekowsky; Marion Kalteis; Mischa Kolibius; Gabriele Schuster; Sabine Wießner (IUBH Internationale Hochschule, 2019)
– Sustainability is an essential topic for industries, governments and consumers around the globe. With the current initiative "Fridays for Future" kicked off by Greta Thunberg sustainability has gathered international momentum. This momentum is also being captured at IUBH, in particular in the Bachelor & Master program "Marketing management". In this paper, six professors at IUBH describe how they empowered and supervised student teams at six different IUBH campuses in Berlin, Düsseldorf, Erfurt, Hamburg, Munich and Vienna to analyze sustainability topics within marketing. More specifically, the paper describes both the professors' teaching approach, their critical reflection as well as the student project outcomes. Within this teaching approach, sustainability was tackled by many different perspectives and industries (e.g., food, packaging, fashion, cosmetics). Based on the research questions, professors varied the research method. Thus, some student teams analyzed sustainable consumer behavior by means of qualitative (e.g., focus groups, interviews) and quantitative market research (e.g., surveys). Other teams acted as entrepreneurs and ideated on sustainable products and services by conducting market analyses and by creating a marketing plan. Overall, this paper gives a holistic view for teaching staff on how to incorporate current topics of sustainability in university curricula in terms of applied student research projects.
Keywords: 650; Lehrforschung; Nachhaltigkeit; Marketing; Hochschuldidaktik; Marktforschung; Interaktive Lehrformen